A framework for risk management decisions in aviation safety at state level. (November 2018) - Rios Insua, D.; Alfaro, C.; Gomez, J.; Hernandez-Coronado, P.; Bernal, F.
Abstract: Aviation is a key industrial sector for global development. Safety is essential for its healthy growth. However its management is pervaded by simplistic methods based on risk matrices. We provide here a framework for risk management decisions in aviation safety at state level. This helps us in identifying the best portfolio that a state agency may implement to improve aviation safety in a country. We illustrate our proposal with a case study. Abstract : Highlights: A framework for risk management decisions in aviation safety is proposed. The methodology relies on sound principles of risk and decision analysis. It is illustrated with a case study.